Viewers in Distress : Race, Gender, Religion, and Avant-Garde Performance at the Turn of the Twenty-First Century - Mihaylova, Stefka G. (Book collections on Project MUSE., 2023)
Conventional notions of avant-garde art suggest innovative artists rebelling against artistic convention and social propriety, shocking unwilling audiences into new ways of seeing and living. Viewers in Distress tells a different story. Beginning in the tumultuous 1990s, after the fall of the Berlin Wall and in the wake of the Los Angeles riots, rebellious spectators in American and British theaters broke with theater decorum and voiced their radical interpretations of shows that were not meant to be radical. In doing so, audiences tried to understand the complex racial, gender, and religious politics of their times, while insisting that liberal societies fulfill their promise of dignity for all. Stefka Mihaylova argues that such non-conforming viewing amounts to an avant-garde of its own: a bold reimagining of how we live together and tell stories of our lives together, aimed to achieve liberalism's promise. In telling this story, she analyzes the production and reception politics of works by Susan-Lori Parks, Sarah Kane, Forced Entertainment, Gurpreet Kaur Bhatti, and Young Jean Lee, as well as non-theatrical controversies such as the conflict over Halloween costumes at Yale in 2015. At the core of spectators' discontent, this book suggests, is an effort to figure out how to get along with people different from ourselves in the diverse U.S. and British societies in which we live.